2014
DOI: 10.5897/ajmr11.1118
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asymptomatic hepatitis B virus surface antigenemia in children in Ilesha, Osun state, South-Western Nigeria

Abstract: Hepatitis B virus (HBV) infection is endemic in sub-Saharan Africa with a range of 8 to 20% prevalence of chronic carriers. Most HBV infections occur early in life by perinatal transmission from the mother to her newborn baby, and horizontal transmission from child to child resulting from blood contact. This study was therefore carried out to assess the prevalence of Hepatitis B virus surface antigenemia (HBsAg) in children born in Ilesha, Osun State, Southwestern Nigeria. A total of 144 children at age range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…The seropositivity of HBsAg in this study was 1.2%. This prevalence is less than most studies carried out in Nigerian children where the prevalence ranged from 4.1% to 44.7% [ 7 – 16 ]. Some of these studies were done in a hospital setting and had fewer sample size compared to the present study.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The seropositivity of HBsAg in this study was 1.2%. This prevalence is less than most studies carried out in Nigerian children where the prevalence ranged from 4.1% to 44.7% [ 7 – 16 ]. Some of these studies were done in a hospital setting and had fewer sample size compared to the present study.…”
Section: Discussionmentioning
confidence: 63%
“…In this study, female children had a higher prevalence than their male counterparts though the difference did not reach the level of significance. Donbraye et al [ 16 ] working in Osun state, south west, Nigeria also showed higher prevalence in female children than males but the difference similarly did not reach significant level. Bukbuk et al [ 13 ] working in northern Nigeria also showed no significant difference between males and females.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, it can be concluded that the distribution of HBV based on gender is not significant. Although a study carried out by Joanah et al (2016) also attests to an increased occurrence of HBV among females by a relative rate of 1.0%, Donbraye et al (2014) also recorded a higher prevalence of HBV in females compared to males in a study carried out in Osun State 18,19 …”
Section: Discussionmentioning
confidence: 97%
“…Several studies in Nigerian children have recorded prevalence rates of hepatitis B surface antigen (HBsAg) ranging from 4.1% to 44.7% varying from one locality to another. Some of these studies however were hospital based with obvious limitations where different screening methods were used [12]. Early diagnosis and treatment can help prevent liver damage.…”
Section: Introductionmentioning
confidence: 99%